Indoor Particulate Matter From Smoker Homes Induces Bacterial Growth, Biofilm Formation, and Impairs Airway Antimicrobial Activity. A Pilot Study - Stapleton, Emma M.; Manges, Robert; Parker, Gavin; Stone, Elizabeth A.; Peters, Thomas M.; Blount, Robert J.; Noriega, Julio; Li, Xiaopeng; Zabner, Joseph; Polgreen, Philip M.; Chipara, Octav; Herman, Ted; et al. (Frontiers in Public Health, 2020)
Background Particulate matter (PM) air pollution causes deleterious health effects; however, less is known about health effects of indoor air particulate matter (IAP). Objective To understand whether IAP influences distinct mechanisms in the development of respiratory tract infections, including bacterial growth, biofilm formation, and innate immunity. Additionally, we tested whether IAP from Iowa houses of subjects with and without recent respiratory exacerbations recapitulated the National Institute of Standards and Technology (NIST) IAP findings. Methods To test the effect of NIST and Iowa IAP on bacterial growth and biofilm formation, we assessed S. aureus growth and P. aeruginosa biofilm formation with and without the presence of IAP. To assess the effect of IAP on innate immunity, we exposed primary human airway surface liquid (ASL) to NIST, and Iowa IAP. Lastly, we tested whether specific metals may be responsible for effects on airway innate immunity. Results NIST and Iowa IAP significantly enhanced bacterial growth and biofilm formation. NIST IAP (whole particle and the soluble portion) impaired ASL antimicrobial activity. IAP from one Iowa home significantly impaired ASL antimicrobial activity (p<0.05), and five other homes demonstrated a trend (p≤0.18) of impaired ASL antimicrobial activity. IAP from homes of subjects with a recent history of respiratory exacerbation tended (p=0.09) to impair ASL antimicrobial activity more than IAP from homes of those without a history respiratory exacerbation. Aluminum and Magnesium impaired ASL antimicrobial activity, while copper was bactericidal. Combining metals varied their effect on ASL antimicrobial activity. Conclusions NIST IAP and Iowa IAP enhanced bacterial growth and biofilm formation. ASL antimicrobial activity was impaired by NIST IAP, and Iowa house IAP from subjects with recent respiratory exacerbation tended to ASL antimicrobial activity. Individual metals may explain impaired ASL antimicrobial activity; however, their combined effect remains elusive.